RELEVANSI PENDIDIKAN KARAKTER DALAM FILM KUNGFU PANDA TERHADAP PENDIDIKAN AGAMA ISLAM - Eko Nur Wibowo (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
This study aims to describe the values of character education in the film Kung Fu Panda and its relevance with Islamic education. This research is qualitative research using descriptive method. The data is taken from the character's dialogue in particular intercultural dialogue involving the main characters. That data is then described and analysed. This research focuses on the educational value of the character in the film.. This research found several values character education that is religious, honest, discipline, hard work, creative, democratic, curiosity, love of the motherland, social care, and responsibility. Values that are relevant to the purpose of the concept of Islamic religious education in shaping attitudes, terpuju (mahmudah morals).